An acyl-CoA:cholesterol acyltransferase (ACAT)-related gene is involved in the accumulation of triacylglycerols in Sacchoromyces cerevisiae. (December 2000) - Sandager, L.; Dahlqvist, A.; Banaś, A.; Ståhl, U.; Lenman, M.; Gustavsson, M.; Stymne, S.
Abstract : The major route for the synthesis of triacylglycerol (TAG) in yeast as well as in all TAG-accumulating organisms has been suggested to occur via the acylation of diacylglycerol (DAG) by acyl-CoA: diacylglycerol acyltransferase (DAGAT). Genes encoding DAGAT have been identified in both plant and animal tissues. These genes show strong sequence similarities to genes encoding acyl-CoA: cholesterol acyltransferase (ACAT). So far no Saccharomyces cerevisiae DAGAT gene has been published; however, two ACAT-like genes, ARE1 and ARE2, are present in the yeast genome. Both these genes have been suggested to be involved in the synthesis of sterol esters. We have now shown that the ARE1 gene in yeast also is involved in the synthesis of TAG, whereas the ARE2 gene is more specifically involved in the synthesis of sterol esters.